2016
DOI: 10.1007/s40261-016-0418-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Ascending-Dose Pharmacokinetics and Safety Evaluation of Baicalein Chewable Tablets in Healthy Chinese Volunteers

Abstract: In dose range of 200-800 mg, multiple-dose oral baicalein administration was safe and well tolerated, dose proportionality was inconclusive, and no serious accumulation of baicalein was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…1). Importantly, two phase I clinical trials of baicalein in healthy Chinese adult volunteers have been completed (Li et al, 2014;Pang et al, 2016) and confirmed that baicalein is safe and well tolerated by healthy subjects. Thus, all of these properties indicate that the therapeutic implications of baicalein may prove successful in slowing or even halting further progression of CNS neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…1). Importantly, two phase I clinical trials of baicalein in healthy Chinese adult volunteers have been completed (Li et al, 2014;Pang et al, 2016) and confirmed that baicalein is safe and well tolerated by healthy subjects. Thus, all of these properties indicate that the therapeutic implications of baicalein may prove successful in slowing or even halting further progression of CNS neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 88%
“…The accumulation index varied from 1.66 to 2.07 for baicalein and from 1.68 to 2.45 for baicalin. In conclusion, in dose range of 200-800 mg, multiple-dose oral baicalein administration was safe and well tolerated, dose proportionality was inconclusive, and no serious accumulation of baicalein was observed (Pang et al, 2016).…”
Section: Clinical Trials Of Baicaleinmentioning
confidence: 78%
“…This suggests baicalein to be considered as solid treatment tool for neurodegenerative diseases including PD. Importantly, baicalein is safe and sufficiently well tolerated by healthy volunteers as evidenced by two phase I clinical trials based on Chinese healthy adult volunteers [74,75]. Therefore, the abovementioned properties of baicalein indicate its potential therapeutic implications in slowing down/ halting the progression of PD.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, another study in Chinese subjects based on placebo-controlled, single-center, and double-blind parallel group investigated the pharmacokinetics, safety, and tolerability of baicalein following multiple-ascending-dose protocol [75]. Volunteers were randomly divided to get placebo treatment (n = 2 per dose regimen) or baicalein (n = 8 per dose regimen).…”
Section: Clinical Trials With Baicaleinmentioning
confidence: 99%
“…Baicalein and oroxylin A (a methylated metabolite of baicalein in human body; Figure b; Zhang et al, ), active flavonoids extracted from the plant Scutellaria baicalensis Georgi radix, contain multiple hydroxyl and/or methoxyl substituents on their B‐rings (Figure b; Lu, Guo, & Zhao, ; Wang et al, ). Moreover, substantial biotransformation between baicalein or oroxylin A and their corresponding glycosides (baicalin and oroxylin A 7‐O‐β‐D‐glucuronide, respectively) was found in human body (Figure b; Pang et al, ; Zhang et al, ). These glycosides also contain the key structural features of inhibiting CYP1B1 (Figure b); however, their inhibitory effects have not been studied.…”
Section: Introductionmentioning
confidence: 99%